The relative importance of left atria reservoir strain compared with components of HFA-PEFF diagnostic algorithm. (3rd October 2022) - Kim, M; Jung, I H; Bae, S
Abstract: Background/Introduction: The relative importance of the left atrial reservoir strain (LARS) compared to the parameters constituting the HFA-PEFF score developed as a diagnostic tool for patients with heart failure with preserved ejection fraction (HFpEF) is not well known. Purpose: We aimed to identify the relative importance of LARS compared with variables associated with HFpEF and HFA-PEFF score including echocardiographic parameters, demographic data, and NT-proBNP. Methods: From August 2021 to March 2022, we obtained data retrospectively from the participants visiting our clinic in a single cardiovascular center. The 1, 252 participants with sinus rhythm and ejection fraction more than 50% were enrolled in the present study (61.8±16.6 years and 55% female). Multivariable regression analysis using backward elimination and random forest analysis, supervised learning algorithm, were performed to identify the relative importance of LARS on the HFA-PEFF score. Results: The median HFA-PEFF score was 3 points (interquartile range 2 to 4 points). Two hundred forty-one subjects (19.2%) had more than 5 points. LARS showed a moderate correlation with the HFA-PEFF score (r=−0.632, p<0.001). In multivariable regression analysis, LARS was independent variable affecting HFA-PEFF score with female sex, left atrial volume index (LAVI), septal e', E over e' (septal), the maximal tricuspid regurgitation velocity (TR-Vmax), left ventricular global longitudinal strain (LV-GLS), NT-proBNP, interventricular septal wall thickness (standardized β=−0.106; P<0.001). In random forest analysis, LARS was a more relatively important variable than TR-Vmax, NT-proBNP, septal E/e', septal e', the major echocardiographic components of HFA-PEFF score estimating more than 5 points of HFA-PEFF score. Conclusions: LA reservoir strain is one of the important factors with components of the HFA-PEFF score which is a useful tool to assess the patients with HFpEF. Funding Acknowledgement: Type of funding sources: None.